Cardiopulmonary resuscitation in small animals. Issue 9 (29th September 2016) - Strachan, Fiona
Abstract : Cardiopulmonary arrest (CPA) is rapidly followed by death unless it is immediately recognised and cardiopulmonary resuscitation (CPR) promptly implemented. Even so, the chances of achieving a favourable outcome are fairly poor. To give the best possible chance of success, veterinary surgeons dealing with small animals should have knowledge of current CPR techniques, with the practice team trained in following a preplanned CPR protocol. This article, which incorporates evidence‐based guidelines produced by the Reassessment Campaign on Veterinary Resuscitation (RECOVER) initiative, describes the causes and recognition of CPA as well as the technique of CPR, including basic and advanced life support and postresuscitative care.